2017
DOI: 10.1080/14767058.2017.1315660
|View full text |Cite
|
Sign up to set email alerts
|

Content fat and calorie of human milk is affected by interactions between maternal age and body mass index

Abstract: The evaluation of over- or under-weighted infants warrants considering both of maternal age and BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 9 publications
2
48
1
1
Order By: Relevance
“…Lactation represents the greatest postnatal energetic expenditure for mammal females [ 31 ], and is directly influenced by the mother’s physical condition. The relationship of body mass to milk macronutrient composition has been extensively considered [ 32 , 33 ]. Especially, very young mothers have fewer bodily reserves available to face simultaneously the costs of lactation and of their own growth [ 34 ].…”
Section: Variation In the Protein Content Of Milk: A Comparative Pmentioning
confidence: 99%
“…Lactation represents the greatest postnatal energetic expenditure for mammal females [ 31 ], and is directly influenced by the mother’s physical condition. The relationship of body mass to milk macronutrient composition has been extensively considered [ 32 , 33 ]. Especially, very young mothers have fewer bodily reserves available to face simultaneously the costs of lactation and of their own growth [ 34 ].…”
Section: Variation In the Protein Content Of Milk: A Comparative Pmentioning
confidence: 99%
“…This issue must be addressed at all stages of life, particularly in women in the reproductive 22 and gestational 23 periods due to the several negative consequences of this condition to the mother-child dyad 23 . Some studies have evaluated the possible impact of overweight on the nutritional composition of human milk 2,20 . However, their results diverge mainly regarding the nutritional content evaluated, the methods to assess the nutritional composition of milk, the type of milk analyzed (colostrum, transitional, and mature), and the control of confounding factors in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study with 80 puerperae, Hahn et al 20 analyzed the concentration of lipids in mature milk using Miris, a piece of equipment already validated for the analysis of human milk 25 . The authors observed that maternal age and nutritional status changed the composition of lipids in human milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the months of lactation as discussed above, the factor showing an association with HM composition in our study was maternal BMI, which was signi cantly positively associated with the fat concentration and energy content in HM. A positive correlation between fat content and maternal BMI has been repeatedly reported [21][22][23][24], while information on the association between maternal BMI and carbohydrate contents remains limited and inconclusive. The same results have been shown by Chang et al [24].…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%